?ION PAIRS AND SOLVENT-SOLUTE INTERACTION: Conductance of Sodium Chloride in Methanol-Hjf) and Glycerol-Hjf) Mixtures at Different Temperatures (Biological Sciences - PJSIR, 2022)
The conductance of sodium chloride over the approximate range of concentration up to 0.02M has been measured in methanol-H20 and glyccrol-HiD mixtures at 25,30,35, and 40°. For mixtures with the same dielectric constant, the association constant, KA' is over an order of magnitude greater in the glycerol mixtures. This mainly is due to effect of hydrogen bond. Glycerol-HjO is more hydrogen bonded solvent than methanol-H20. Also, KA values increase as the proportion of methanol or glycerol increases in the mixture. TIle thermodynamic parameters ~Ho, ~Go, and ~So were also calculated. It turned out that the entire process of ionic association in those systems are endothermic ones. The results are discussed on the basis of ion solvent interaction.